Entrepreneurial orientation and performance in a developing country: Strategic entrepreneurship as a mediator. Issue 4 (13th July 2020) - Soomro, Bahadur Ali; Shah, Naimatullah
Abstract: The present paper aims to determine the mediatory role of strategic entrepreneurship between entrepreneurial orientation and performance in a developing country. The study found a positive and significant influence of entrepreneurial orientation on strategic entrepreneurship and financial performance of the firms. Entrepreneurial orientation has no significant effect on non‐financial performance. The strategic entrepreneurship mediates the relationship between entrepreneurial orientation and financial performance rather than non‐financial performance. The strategic entrepreneurship explored as a significant predictor of both financial and non‐financial performance of the firms. The findings of the study would provide basic knowledge about the factors that may enhance firm performance.